2009
DOI: 10.1007/s00421-009-1328-7
|View full text |Cite
|
Sign up to set email alerts
|

Skin microvascular reactivity in trained adolescents

Abstract: Whilst endothelial dysfunction is associated with a sedentary lifestyle, enhanced endothelial function has been documented in the skin of trained individuals. The purpose of this study was to investigate whether highly trained adolescent males possess enhanced skin microvascular endothelial function compared to their untrained peers. Seventeen highly and predominantly soccer trained boys (V(O)(2)(peak): 55 +/- 6 mL kg(-1) min(-1)) and nine age- and maturation-matched untrained controls (V(O)(2)(peak): 43 +/- 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
(107 reference statements)
0
19
1
1
Order By: Relevance
“…In contrast, responses to sodium nitroprusside were not different between groups. Similarly, Roche et al (172) recently reported an enhanced skin blood flow response to local heating in physically active children (aged 13–15 yr) compared with age-matched (less active) controls. Using a longitudinal study design, Wang (204) evaluated endothelium-dependent and -independent cutaneous vascular responses in sedentary but otherwise healthy males before and after 8 wk of exercise training.…”
Section: Effects Of Exercise Training On the Endothelium Of Noncontramentioning
confidence: 77%
“…In contrast, responses to sodium nitroprusside were not different between groups. Similarly, Roche et al (172) recently reported an enhanced skin blood flow response to local heating in physically active children (aged 13–15 yr) compared with age-matched (less active) controls. Using a longitudinal study design, Wang (204) evaluated endothelium-dependent and -independent cutaneous vascular responses in sedentary but otherwise healthy males before and after 8 wk of exercise training.…”
Section: Effects Of Exercise Training On the Endothelium Of Noncontramentioning
confidence: 77%
“…Namely, a recent study performed in adolescents showed an enhanced endothelium-dependent vasodilation in nonglabroous skin in the group of trained subjects (Roche et al, 2010). Also, in the group of postmenopausal women who underwent a 48-week regime of aerobic exercise training the endothelium-dependent and -independent vasodilation was enhanced as well as the response to local heating (Hodges et al, 2010).…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 94%
“…Children and adolescents rely more on peripheral blood redistribution (radiative and conductive cooling) rather than sweating (evaporative cooling) to maintain thermal equilibrium. There is also evidence that adolescents who undertake regular training adapt by enhanced peripheral vasodilation (Roche et al, 2010) which is likely to improve nonevaporative cooling. While the timing of the transition from child-like to adult-like thermoregulatory mechanism is likely to be related to pubertal development, it appears that these changes do not become physiologically evident until puberty has been completed (Falk et al, 1992).…”
Section: Fluid Recommendations For Adolescent Athletesmentioning
confidence: 96%